2014
DOI: 10.1063/1.4875356
|View full text |Cite
|
Sign up to set email alerts
|

Highly oriented, free-standing, superconducting NbN films growth on chemical vapor deposited graphene

Abstract: NbN films are grown on chemical vapor deposited graphene using dc magnetron sputtering. The orientation and transition temperature of the deposited films is studied as a function of substrate temperature. A superconducting transition temperature of 14 K is obtained for highly oriented (111) films grown at substrate temperature of 150 °C, which is comparable to epitaxial films grown on MgO and sapphire substrates. These films show a considerably high upper critical field of ∼33 T. In addition, we demonstrate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
2
3
1
Order By: Relevance
“…larger diffusion constant / lower resistivity. Indeed, the resistivities ρ xx ∼ 60 µΩcm we observe are significantly lower than previously reported [10,26,27]. One should note, however, that the above formula yields B c2 (0) ∼ 2.5 T for our films, a significantly lower field than the value extracted from Fig.…”
Section: Analysis and Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…larger diffusion constant / lower resistivity. Indeed, the resistivities ρ xx ∼ 60 µΩcm we observe are significantly lower than previously reported [10,26,27]. One should note, however, that the above formula yields B c2 (0) ∼ 2.5 T for our films, a significantly lower field than the value extracted from Fig.…”
Section: Analysis and Discussioncontrasting
confidence: 62%
“…The upper critical field B c2 is very similar for all of our films, but much lower than for other films with T c higher than 14 K reported in the literature [10,26,27]. In the dirty limit -defined by ℓ ≪ ξ(0) -B c2 (0) is related to resistivity and diffusion constant via B c2 (0) = 0.69T c 4k B /πeD = 0.69T c 4ek B N V ρ xx /π [28].…”
Section: Analysis and Discussionsupporting
confidence: 60%
“…Primarily, dimensionality of a superconducting film on a dielectric substrate decreases with the decrease of the film thickness d. Dependences of the critical temperature on the thickness of superconducting films were intensively studied both experimentally and theoretically. It has been observed that in Nb [1,2], NbN [3,4,5], TaN [6], TiN [7], Pb [8], Bi [9], WSi [10] and other elementary and compound superconducting films critical temperatures decrease with the decrease in their thicknesses. It is well established that for films prepared by optimized technology and having thicknesses much larger than the coherence length the transition temperature TC is independent of the thickness and equals TC of corresponding bulk specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Free-standing films without solid substrates are very useful for achieving flexibility, selective formability, and large-scale applicability. To demonstrate the flexibility and formability, a free-standing superconductor film was prepared as a new application of our proposed paste technology. The free-standing films were prepared by the method described above using NbN paste with a high T c .…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…The proposed technology is also fundamental for fabricating flexible superconducting free-standing films. This technology is expected to be useful for creating superconducting connections , that maintain both superconductivity and mechanical links between wires and thin films and for superconducting interconnect technology in multilayered devices that electrically and mechanically connect the upper and lower layers, which can act as adhesives with superconducting properties.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%